Clinical characteristics of persistent headaches after the first-ever ischemic stroke (follow-up of 529 patients) - Elena R. Lebedeva; Anton V. Ushenin; Denis V. Gilev; Jes Olesen (ZAO "Consilium Medicum", 2023)
Background. Although persistent headaches are a common post-stroke pain syndrome, the epidemiology and clinical features of persistent headache after first-ever ischemic stroke have not been considered previously. There is no exact data on how often headache attributed to stroke persists for more than 3 months, i.e. meets the criteria for persistent headache after stroke and what are their distinctive clinical features. The tasks of our study were: to analyze the occurrence/incidence of persistent headaches after the first-ever ischemic stroke; to determine clinical characteristics and types of persistent headaches in comparison with headaches at the onset of stroke. Materials and methods. The study included 550 patients (mean age 63.1 years, 54% men) with first-ever ischemic stroke, of which 529 patients were followed up for at least three months after the stroke. Standardized semi-structured interview forms were used to assess these headaches during professional face-to-face interviews at the onset of stroke and 3 months after the stroke using telephone interview by neurologist. Results. Among 529 follow up patients 55 (10.4%) had persistent headaches after first-ever ischemic stroke. Among these 55 patients 34 patients had persistent new-type headaches which arose for the first time during the onset of stroke, they included predominated migraine-like headaches (n=20), tension-type-like headaches (n=9) and thunderclap-like headaches (n=5). 21 patients had persistent headaches with altered characteristics: predominated tension-type-like headaches (n=16), and less common migraine-like headaches (n=5). Persistent headaches after stroke had the following characteristics compared to headaches at onset of stroke: severe headache intensity, a gradual decrease of occurrence of accompanying symptoms (photo- and phonophobia; p=0.03), the transition of unilateral headaches in bilateral (p=0.004), the presence of headaches 15 days per month in 30.9% of the patients. Conclusion. Persistent post-stroke headaches represent a persistent pain syndrome with severe intensity and frequency of attacks, which requires their further study and creation of guidelines for their management.